2011
DOI: 10.3998/ark.5550190.0012.915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solvent, excitation wavelength, and concentration on the photobehavior of some diazonaphthoquinones

Abstract: Diazonaphthoquinones (DNQs) are the photoactive components of resists used in the fabrication of integrated circuits. Exposed to radiation these compounds release molecular nitrogen undergoing a ring contraction (Wolff rearrangement). In this work the photobehavior of three compounds bearing two and three chromophoric DNQ units has been studied. Photochemical quantum efficiencies of reactant disappearance have been determined in acetonitrile at 290 K and in ethanol/methanol (4/1, v/v) solid matrix at 80 K, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Three derivatives, ( 44) to ( 46), bearing two or three chromophoric diazonaphthoquinone units were investigated in acetonitrile (ca. 2 × 10 −5 M) under various monochromatic radiations at 254, 350, 399, and 423 nm at 290 and 80 K. It was found that the photoconversion quantum yields, measured by two different methods, varied between 11 and 55% for the individual molecules over the selected series of irradiation wavelengths [131]. By irradiating the 𝑆 → 𝑆 transition of a spirooxazine derivative (47…”
Section: φ = δ𝐴 𝑉 𝑃 δ𝑡 (1 − 10 ) 𝜀mentioning
confidence: 99%
“…Three derivatives, ( 44) to ( 46), bearing two or three chromophoric diazonaphthoquinone units were investigated in acetonitrile (ca. 2 × 10 −5 M) under various monochromatic radiations at 254, 350, 399, and 423 nm at 290 and 80 K. It was found that the photoconversion quantum yields, measured by two different methods, varied between 11 and 55% for the individual molecules over the selected series of irradiation wavelengths [131]. By irradiating the 𝑆 → 𝑆 transition of a spirooxazine derivative (47…”
Section: φ = δ𝐴 𝑉 𝑃 δ𝑡 (1 − 10 ) 𝜀mentioning
confidence: 99%
“…Entretanto o substituinte OCH 2 CH 3 causa um pronunciado red shift de 23 nm, indicando que ocorre uma interação mais efetiva entre o grupo doador de elétrons OCH 3 e o grupo aceitador C=O que se encontra no centro da molécula ambos conectados por conjugação, ocasionando uma diminuição na energia de transição observado na absorção linear. Por outro lado, os outros Como as moléculas são idênticas estruturalmente, a absortividade molar pode ser dividida em dois termos,72 um referente ao substituinte e outro para o resto da molécula, os quais fornecem a absortividade molar total da molécula. Desta forma, observamos que o radical metil na configuração para contribui com uma absortividade menor, indicando que este radical de alguma forma reduz a intensidade de absorção da Absortividade molar (ɛ(λ)) obtido para as moléculas do grupo 1 dissolvidas em DMSO e os valores correspondentes do comprimento de onda para a banda de absorção mais intensa (λ MAX ).…”
unclassified